2006
DOI: 10.1093/jxb/erl065
|View full text |Cite
|
Sign up to set email alerts
|

HaloTagTM: a new versatile reporter gene system in plant cells

Abstract: HaloTag Interchangeable Labeling Technology (HaloTag) was originally developed for mammalian cell analysis. In this report, the use of HaloTag is demonstrated in plant cells for the first time. This system allows different fluorescent colours to be used to visualize the localization of the non-fluorescent HaloTag protein within living cells. A vector was constructed which expresses the HaloTag protein under the control of the 35S promoter of cauliflower mosaic virus. The functionality of the HaloTag construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…[171] HaloTag is am odified haloalkane dehalogenase developed by Wood and co-workers that covalently labels itself with chloroalkanes with fast kinetics and high selectivity. [172,173] In CAPA ,t he cells are first pulsed with ac hloroalkane-tagged molecule of interest, which covalently blocks HaloTag if it reaches the cytosol. Chasing with ac hloroalkane-dye allows quantitation of unreacted HaloTag using flow cytometry in 96-well plates.C APAi sn ot tag-free,a nd thus has all the liabilities of atag-based assay described above.…”
Section: Methods For Measuring Cell Penetrationmentioning
confidence: 99%
“…[171] HaloTag is am odified haloalkane dehalogenase developed by Wood and co-workers that covalently labels itself with chloroalkanes with fast kinetics and high selectivity. [172,173] In CAPA ,t he cells are first pulsed with ac hloroalkane-tagged molecule of interest, which covalently blocks HaloTag if it reaches the cytosol. Chasing with ac hloroalkane-dye allows quantitation of unreacted HaloTag using flow cytometry in 96-well plates.C APAi sn ot tag-free,a nd thus has all the liabilities of atag-based assay described above.…”
Section: Methods For Measuring Cell Penetrationmentioning
confidence: 99%
“…[112] Das Chloralkan-Penetrationsassay,o der kurz CAPA ,n utzt eine stabile Zelllinie,d ie das HaloTag-Enzym im Zytosol exprimiert. [172,173] Bei CAPA werden Zellen zunächst mit dem zu untersuchenden, Chloralkan-markierten Molekülg epulst, das bei Erreichen des Zytosols HaloTag kovalent blockiert. [172,173] Bei CAPA werden Zellen zunächst mit dem zu untersuchenden, Chloralkan-markierten Molekülg epulst, das bei Erreichen des Zytosols HaloTag kovalent blockiert.…”
Section: Methoden Zur Messung Der Zellpenetrationunclassified
“…[171] HaloTag ist eine modifizierte Halogenalkan-Dehalogenase,die von Wood und Mitarbeitern entwickelt wurde und mit schneller Kinetik und hoher Selektivitätd urch Chloralkane markiert wird. [172,173] Bei CAPA werden Zellen zunächst mit dem zu untersuchenden, [125,[179][180][181][182] Die Entscheidung, wie ein Peptid zu modifizieren ist, um es intrinsisch zellgängig zu machen, hängt von seiner Grçße, Ladung und Hydrophobie ab.E in Peptid kann einem passiven Penetrationsmechanismus unterliegen, wenn es eher klein ist -d efiniert durch ein Molekülvolumen < 1500 3 entsprechend einem Peptid von < 1100-1200 Dalton. [65,135] Füre ine passive Zellpenetration ist auch die Zahl der solvensexponierten Wasserstoffbrückendonoren begrenzt.…”
Section: Methoden Zur Messung Der Zellpenetrationunclassified
“…Of those which permit intracellular labelling, the proprietary SNAP TM and CLIP TM tag systems based on O 6 -alkylguanin-DNA alkyltransferase (New England Biolabs; [67,68]), HaloTag TM (Promega; [69]), based on haloalkane dehalogenase, and LigandLink TM , based on Escherichia coli dihydrofolate reductase (ActiveMotif; [70]), all utilize the reaction between small enzymes and substrate analogues to link a fluorophore covalently to a protein of interest, but provide only a modest size advantage over GFP (27 kDa) with tag molecular masses between 18 and 33 kDa. Only HaloTag TM has been tested in plants, with good tissue permeability [71]. A tag based on the human immunophilin FKBP12 (FK506-binding protein 12) [72,73] adds only 12 kDa, but has not been tested in plants yet.…”
Section: Labelling Fusion-intolerant Viral Proteins With Small Fluorementioning
confidence: 99%
“…Non-fluorescent probes are available for blocking the pre-existing protein pool instead of changing the label colour, but the tissue still has to be washed to remove non-specific fluorescence. Lang et al [71] have reported washing times of between 4 and 18h for HaloTag TM , the only one of these systems tested in plants. Unless the tissue is fixed, these times are too long for detecting translation sites.…”
Section: Fluorescent Highlighter Proteins and Tag-probe Pulse-chase Lmentioning
confidence: 99%